Envisioning Community Economic Development Through an Indigenous-Led Social Enterprise in Ka’a’gee Tu First Nation, Northwest Territories - Rodriguez-Reyes, Laura; Temmer, Jennifer; Simba-Canadien, Maverick; Spring, Charlotte; Simba, Ruby; Spring, Andrew (Journal of Aboriginal Economic Development)

(untitled) (CANDO, 2025)
The Ka’a’gee Tu First Nation, in Kakisa, Northwest Territories, is cultivating food to strengthen their food systems against multifaceted threats posed by colonization, climate change, and socioeconomic disparities. Community efforts to grow food are new and stand as an adaptation response to their changing food system. Although establishing food-growing initiatives has been a gradual process, their success is now evident with substantial quantities of food being produced. This research addresses the need for a sustainable food distribution model in Kakisa to ensure food is accessible to the community. Using a participatory action research approach, community members shared their vision, leading to the exploration of an Indigenous-led economic model merging Western approaches with Indigenous values. Kakisa’s enterprise will support food distribution systems, including a store, and act as a space to host social gatherings, facilitate Traditional Knowledge workshops, and share food. The community’s vision of an Indigenous-led social enterprise embodies a holistic approach to economic development that emphasizes social bonding and community well-being over pure economic activities. Accomplishing this vision requires continuous efforts toward fostering collaboration, nurturing cultural resurgence, and empowering Indigenous leadership within economic development.